The Effect Disaster Literacy on Students Preparedness Mitigating Tsunami in Coastal Area Pangandaran - Syifa Nuraziz; Enok Maryani; Ahmad Yani (Jurnal Pendidikan Geografi Gea, 2023)
The potential for a tsunami disaster in Indonesia is very high. Pangandaran has many residential areas and school buildings that stand along the coast of the Indian Ocean. Disaster literacy studies are an alternative in disaster studies or studies, especially in the realm of tsunami disaster mitigation. In this research, the method used was to use a descriptive method with a quantitative approach analysis.. With the result of the study showing that: 1)  level of disaster literacy at the elementary school (SD) is Enough category. The secondary school (SMP) is result Enough category. and the high school (SMA) result is Enough category. 2) level of preparedness disaster at the elementary school SD is Ready category. The secondary school (SMP) is result Ready category. and the high school (SMA) result is Almost Ready category. 3) The effect of disaster literacy on student preparedness mitigating tsunami disaster is The percentage of results from the test of the effect of disaster literacy on student preparedness in mitigating tsunamis, namely Identifying disasters by 87%, Understanding disasters by 86%. Analyzed disasters by 72%, and Produced and Communicated disasters by 69%